Lateral rectus muscle recession and the vertical palpebral fissure height: to do or not to do inter-muscular septum dissection? - Abtahi, Mohammad Ali (Int J Ophthalmol, 2018)
In this study, we aimed to evaluate changes of vertical palpebral fissure height (VPFH) after unilateral lateral rectus muscle recession. Twenty-five and twenty-six patients who were candidates for lateral rectus muscle recession were assigned into “with” and “without” intermuscular septum dissection study arms. The VPFH was measured at one-day before surgery and in two weeks and three months, postoperatively. Three months after surgery, significant increase of VPFH was observed in both groups (Paired t-test; P=0.005). Also, less widening of VPFH was observed in “with intermuscular septum dissection” group (Change in VPFH in “with intermuscular septum dissection” vs “without intermuscular septum dissection” groups: 0.48 mm vs 1.34 mm; ANCOVA test; P<0.001). However, such results were not observed two weeks post-operatively (Change in VPFH in “with intermuscular septum dissection” vs “without intermuscular septum dissection” groups: -0.28 mm vs 0.28 mm; ANCOVA test; P=0.302). Intermuscular septum dissection is recommended in lateral rectus muscle recession to partially prevent the undesirable increment of VPFH.